Modeling the impact of social problem-solving deficits on depressive vulnerability in the broader autism phenotype - Jackson, Scott L. J.; Dritschel, Barbara (Research in Autism Spectrum Disorders, 2016)
The social communication and interaction deficits associated with the autism phenotype can have serious emotional consequences for individuals on the autism spectrum. This can be particularly true during young-adulthood, a period of increased social demands and expectations. The current study investigated the specific role of social problem-solving deficits as a mediator in the relationship between autism phenotype severity and depressive symptomology in young-adults. A sample of 230 university students (48% male) ranging in age from 18 to 30 (M=21.30, SD=2.48) were assessed on autism phenotype expression (Autism-Spectrum Quotient), social problem-solving ability (Social Problem-Solving Inventory, Revised) and depressive symptomology (Beck’s Depression Inventory). Results indicated that deficient social problem-solving skills account for a significant portion of the depressive symptomology associated with increased autism phenotype expression. Path model analysis output suggested that increased expression of the social components of the autism phenotype are associated with both ineffective social problem-solving styles and attitudes, while increased detail orientation discourages the use of an impulsive problem-solving style. The findings of this investigation provide preliminary evidence suggesting that programs designed to improve social problem-solving skills could be beneficial in the reduction of depressive vulnerability for young-adults on the autism spectrum.
Keywords: Autism phenotype expression; Autism-Spectrum Quotient (AQ); Depression; Path model analysis; Social problem solving; University students; dept.aa

Influence of Diphenhydramine HCl and Caffeine on Embryonic Development and Adult Reproductive Success of the Freshwater Gastropod Helisoma trivolvis - Sanchez, Diana; Prezant, Robert S. (American Malacological Bulletin, 2016)
Diphenhydramine HCl (DH) and caffeine are commonly detected contaminants in waterways and drinking water nationwide (U.S.A.) and yet little is known of their influence on the development of aquatic molluscs. The antihistamine diphenhydramine blocks the chemical effects of histamine by inhibiting the re-uptake of serotonin (5-HT). Caffeine can influence the regulation of calcium (Ca2 ) and neurotransmitters, such as 5- HT, by inhibiting the re-uptake of adenosine. Serotonin receptor-mediated signaling is key during embryonic development in the freshwater snail Helisoma trivolvis (Say 1816). Embryonic development rates of H. trivolvis depend upon external conditions such as oxygen concentration and temperature. We examine the effects of diphenhydramine (DH) and caffeine on development and reproductive potential of this common aquatic snail. Concentrations of DH at 40.0, 50.0 and 60.0 µM affect the in-capsule embryonic development and hatching rate. Caffeine at 40.0, 50.0 and 60.0 µM show no influence to the hatching rates; however, these caffeine concentrations influence the in-capsule embryonic rotation rate. Eight-month observations of adult H. trivolvis reproductive activities show no influence in number of egg masses deposited when exposed to test concentrations of DH or caffeine.
Keywords: dept.aa; peer-reviewed